Academic entrepreneurial intention: the role of gender. Issue 1 (13th March 2017) - Miranda, F. Javier; Chamorro-Mera, Antonio; Rubio, Sergio; Pérez-Mayo, Jesús
Abstract : Purpose: The purpose of this study is firstly to analyze whether the determining factors of the entrepreneurial intention of academics are the same for men and women and test whether their degree of importance varies depending on gender, and secondly to test whether the lesser entrepreneurial intention of women detected in previous studies is because of the lesser presence of the determining factors of entrepreneurial intention among women or, on the contrary, is determined by the existence of implicit barriers that do not depend on these factors. Design/methodology/approach: After conducting a survey on a sample of 1, 178 academics, the results of a linear regression model confirm the hypothesis that female academics have less of an entrepreneurial intention. Findings: Moreover, through the Blinder–Oaxaca decomposition, it is observed that this lesser female entrepreneurial behavior is not because of the absence of any of the factors considered as determinants of entrepreneurial intention, but instead is related to the existence of implicit barriers for women that influence their entrepreneurial intention. Originality/value: To the best of the authors' knowledge, this is the first time that a study of this nature has been conducted internationally. Unlike other studies on academic entrepreneurship, the authors do not restrict the sample to one or two universities but rather aim the study at all universities in Spain and, therefore, at all academics from all branches of knowledge.